High‐Q Polymer Microcavities Integrated on a Multicore Fiber Facet for Vapor Sensing. Issue 20 (30th July 2019) - Zhang, Siyao; Tang, Shui‐Jing; Feng, Shengfei; Xiao, Yun‐Feng; Cui, Wanyin; Wang, Xinke; Sun, Wenfeng; Ye, Jiasheng; Han, Peng; Zhang, Xinping; Zhang, Yan
Abstract: The further development of "lab on fiber" technology demands more powerful optical microsystems and optical fibers with special functions to create sensors with better performance. Whispering gallery microcavities (WGMs) made of different materials with high quality factors show very good sensitivity to gases, nanoparticles, and biocomponents. However, realizing the excitation and detection of the resonant modes of WGMs on the facets of optical fibers is still a great challenge. This work employs the advanced 3D manufacturing technology of two‐photon lithography to fabricate an optical microsystem on the end facet of a multicore optical fiber, which enables excitation and detection of whispering gallery modes on the end facet of an optical fiber. Whispering gallery modes with high quality factors are observed, and the sensing characterization of this device for vapors of three types of volatile organic compounds is investigated. Such optical fiber vapor sensors can be applied in the fields of medical care, environmental monitoring and chemical manufacturing. Additionally, the out‐of‐plane light coupling strategy may be useful for the design of integrated optical circuits on chips. Abstract : High‐ Q polymer whispering gallery microcavities (WGMs) with receptacle‐type ports on a multicore fiber facet for vapor sensing applications have been achieved. Just like the diodes in the integrated circuits, such a configuration design of the optical microsystem may be a building block for more compact devices which are based on integrated WGMs sensing array.